Technological, pedagogical, and content knowledge of diploma in professional education graduates teaching biology - Jleian Mard Loseñara; Richard R. Jugar (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Content, pedagogy, and technology knowledge are central to effective teaching. Moreover, the interaction and integration of these knowledge bases challenge teachers, especially non-teacher education graduates including diploma professional education (DPE) graduates. Utilising adapted instruments, this study investigated the teaching competence of biology teachers who are DPE graduates, specifically their Technological, Pedagogical, Content Knowledge (TPACK) and Biology teaching competence to design a teacher professional development (TPD) programme. Most teachers were BS Nursing graduates with professional teaching licenses and teaching experience ranging from 3 to 10 years. Also, most teachers received between one to five TPDs focused on biology, pedagogy, and technology. Among the TPACK components, the teachers perceived that they were least competent in pedagogical knowledge (PK) and pedagogical content knowledge (PCK). Although the teachers agreed on their perceived overall TPACK competence, there is still an avenue to strengthen their TPACK. Teachers also believed that they were least competent in biological cellular processes. Need-based teacher professional development programmes are recommended to enhance Biology teachers’ TPACK, and ultimately, biology education.